Cm‐p5: an antifungal hydrophilic peptide derived from the coastal mollusk Cenchritis muricatus (Gastropoda: Littorinidae). Issue 8 (28th April 2015) - López‐Abarrategui, Carlos; McBeth, Christine; Mandai, Santi M.; Sun, Zhenyu J.; Heffron, Gregory; Alba‐Menéndez, Annia; Migliolo, Ludovico; Reyes‐Acosta, Osvaldo; García‐Villarino, Mónica; Nolasco, Diego O.; Falcão, Rosana; Cherobim, Mariana D.; et al.
Abstract : Antimicrobial peptides form part of the first line of defense against pathogens formany organisms. Current treatments for fungal infections are limited by drug toxicity and pathogen resistance. Cm‐p5 (SRSE‐LIVHQRLF), a peptide derived from the marine mollusk Cenchritis muricatus peptide Cm‐p1, has a significantly increased fungistatic activity against pathogenic Candida albicans (minimal inhibitory concentration, 10 μg/ml; EC50, 1.146 μg/ml) while exhibiting low toxic effects against a cultured mammalian cell line. Cm‐p5 as characterized by circular dichroism and nuclear magnetic resonance revealed an α‐helical structure in membrane‐mimetic conditions and a tendency to random coil folding in aqueous solutions. Additional studies modeling Cm‐p5 binding to a phosphatidylserine bilayer in silico and isothermal titration calorimetry using lipid monophases demonstrated that Cm‐p5 has a high affinity for the phospholipids of fungal membranes (phosphatidylserine and phosphatidylethanolamine), only moderate interactions with a mammalian membrane phospholipid, low interaction with ergosterol, and no interaction with chitin. Adhesion of Cm‐p5 to living C. albicans cells was confirmed by fluorescence microscopy with FITC‐labeled peptide. In a systemic candidiasis model in mice, intraperitoneal administration of Cm‐p5 was unable to control the fungal kidney burden, although its low amphiphaticity could be modified to generate new derivatives with improved fungicidal activity and stability.—López‐Abarrategui, C., McBeth, C., Mandai, S. M., Sun, Z. J., Heffron, G., Alba‐Menéndez, A., Migliolo, L., Reyes‐Acosta, O., Garcia‐Villarino, M., Nolasco, D. O., Falcão, R., Cherobim, M. D., Dias, S. C., Brandt, W., Wessjohann, L., Starnbach, M., Franco, O. L., Otero‐González, A. J. Cm‐p5: an antifungal hydrophilic peptide derived from the coastal mollusk Cenchritis muricatus (Gastropoda: Littorinidae). FASEB J. 29, 3315‐3325 (2015). www.fasebj.org